ФОРМУВАННЯ НАЦІОНАЛЬНОЇ СВІДОМОСТІ ПІДРОСТАЮЧОГО ПОКОЛІННЯ ЗАСОБАМИ ВИВЧЕННЯ ОБРЯДІВ ТА ТРАДИЦІЙ УКРАЇНСЬКОГО НАРОДУ (Педагогіка вищої та середньої школи, 2022)
The article investigates the problem of transmitting generally accepted cultural values of the Ukrainian people and the specific character of its national word view. These two grounds are of primary importance and make an essential basis for upbringing personal qualities of a Ukrainian citizen for the further development of the national education.